Peran Pelatihan Dalam Meningkatkan Produktivitas dan Kualitas Sumber Daya Manusia Untuk Menghadapi Tantangan Global - Pangestu, Agung Hutomo; Ukhra, Akdari; Kurniawan, Chairul Iqbal; Herman, Muhammad Gibran Yulion; Kristianto, Rio; S, Saridawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Globalization is a process of building organizational and communication systems among world communities to follow the same systems and various rules. Globalization itself has special characteristics, namely changes in the form of technological development and progress, this has resulted in the emergence of dependency between countries related to economic production and global markets, increased mutual problems of countries in the world, as well as cultural exchanges and interactions between world citizens. This happens because the needs of economies throughout the world tend to be the same and diverse. This is of course a challenge for companies to be able to compete in an increasingly tight global market. One way to face global challenges in the economic sector like this is to provide training to employees. Training for employees is a part of the business which aims to enable employees to improve and develop knowledge. This training itself is carried out after the company accepts new employees or can be carried out for existing employees with the aim of increasing productivity and the quality of the resources owned by the employee. An employee must have skills and abilities that are in accordance with the company's goals to be able to compete in the global marketThe results of this research are that the role of training carried out by the company is very important to increase the productivity and quality of human resources within the company and of course it is important for the employees themselves to develop abilities and skills that are useful for developing the company's career and goals to be able to compete with the market global.